A Combination of 10% Gambier Extract and 0.0048% Fluoride Toothpaste as An Alternative Antifungal Therapy - Pudji Handayani; Muhammad Naufal Denhari Aflah; Siti Rusdiana Puspa Dewi (Publikasi Indonesia, 2022)
Poor oral hygiene might lead to Candida albicans infection. Since long term used of synthetics antifungal therapy could lead to fungal resistance, an alternative of antifungal therapy was needed. It has been reported that Gambier (Uncaria gambir ROXB) contains catechins and tannins which have antifungal effects invitro, but research using Gambier extract as a toothpaste for daily oral hygiene maintenance has not established. This study was done to determine the antifungal effect and the synergy of the combination of 10% gambier and fluorides in toothpaste preparation against Candida albicans. A true experimental laboratory study with a post-test-only design group was established. Three groups namely 10% gambier extract toothpaste, the combination of 10% gambier extract and 0.0048% fluorides toothpaste, lastly the 0.0048% fluoride toothpaste were tested. Gambier extract was obtained using the soxhletation method and the separation of the solvent from the extract was carried out by the distillation method. Agar Well method antifungal test was used to measure the inhibition zone value of tested groups. Data were analyzed using one-way Anova. Inhibition test of tested groups showed that only combination of gambier and fluorides toothpaste was effective in inhibiting Candida albicans with an average inhibition zone value of 8.35 mm. Toothpaste preparation of 10% Gambier extract and 0.0048% fluorides combination produce a synergistic therapeutic effect in antifungal therapy.